Diseño de una solución semiautomática en el proceso de producción del pan de arroz (2020)
The regional context of the rice snack is presented, as a cultural heritage of the Meta department. Subsequently, describe the artisan process and the threads necessary for its manufacture, and from the previous one, analyze and identify the threads that are susceptible to conversion into automated processes. Once the sub process to be automated has been identified, the design of a semi-automatic solution will be considered, which; encourage an increase in production levels by minimizing the time required in the batch production of rice snacks, and adding, the dead times of operation.